HELMINTH PARASITES OF GOATS AND SHEEP AT SLAUGHTER HOUSE IN LAFIA, NASARAWA STATE, NIGERIA - Aliyu, A. A.; Maikenti, J. I.; Aimankhu, O. P.; Ayuba, S. O.; Ahmed, H. O.; Haruna, A.; Idris, Abdulrazak Muhammad (FUDMA JOURNAL OF SCIENCES, 2020)
Helminth parasites have been recognized as one of the major constraints to both goat and sheep production in Nigeria and other developing countries. A study aimed to determine helminth parasites of goats and sheep at slaughter in Lafia from June to July 2019. Two hundred fecal samples were collected and analyzed from 100 goats and 100 sheep using the direct smear method. The fecal sample examined revealed an overall prevalence of 155(77.5%), with goat having 80(80.0%), sheep 75(75.0%). Thirteen helminth parasites were found with nematode the most prevalent 103(66.5%), trematode had 35(22.6%), and cestode the least with 17(10.1%) and there was a statistically significant difference among the parasites (P<0.001). According to sex, females 59(43.7%) were more infected than males 25(38.5%) and there was a statistically significant difference (P<0.001). Age of sampled animals (Goat and Sheep) shows that <1 year had 28(18.1%), younger animals within the ages of <2 years 65(41.9%) were more infected with helminth parasites than adult animals from <3 years (13.5%) and >33 had 25(16.1%) and there was no statistically significant difference in age (P>0.312). According to breeds, the West African dwarf goats and sheep were more infected 104(52%), the Fulani breeds 73(36.5%) and the least was Balami sheep with 13(6.5%), Uda goat 10(5%) and there was a statistically significant difference among the breeds (P<0.001). This study revealed a high prevalence of helminth parasites of goat and sheep at slaughter in Lafia which may reduce productivity. It is recommended that goats and sheep be dewormed regularly.